Quantitative proteomic analysis identified differentially expressed proteins with tail/rump fat deposition in Chinese thin- and fat-tailed lambs. - Jilong Han; Tingting Guo; Yaojing Yue; Zengkui Lu; Jianbin Liu; Chao Yuan; Chune Niu; Min Yang; Bohui Yang (PLoS ONE, 2021)
Tail adipose as one of the important functional tissues can enhance hazardous environments tolerance for sheep. The objective of this study was to gain insight into the underlying development mechanisms of this trait. A quantitative analysis of protein abundance in ovine tail/rump adipose tissue was performed between Chinese local fat- (Kazakh, Hu and Lanzhou) and thin-tailed (Alpine Merino, Tibetan) sheep in the present study by using lable-free approach. Results showed that 3400 proteins were identified in the five breeds, and 804 were differentially expressed proteins, including 638 up regulated proteins and 83 down regulated proteins in the tail adipose tissues between fat- and thin-tailed sheep, and 8 clusters were distinguished for all the DEPs' expression patterns. The differentially expressed proteins are mainly associated with metabolism pathways and peroxisome proliferator activated receptor signaling pathway. Furthermore, the proteomics results were validated by quantitative real-time PCR and Western Blot. Our research has also suggested that the up-regulated proteins ACSL1, HSD17β4, FABP4 in the tail adipose tissue might contribute to tail fat deposition by facilitating the proliferation of adipocytes and fat accumulation in tail/rump of sheep. Particularly, FABP4 highly expressed in the fat-tail will play an important role for tail fat deposition. Our study might provide a novel view to understanding fat accumulation in special parts of the body in sheep and other animals.